2003
DOI: 10.1002/yea.1016
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of the cysteine residues and the repetitive sequence of Saccharomyces cerevisiae Pir4/Cis3: the repetitive sequence is needed for binding to the cell wall β‐1,3‐glucan

Abstract: Identification of PIR/CIS3 gene was carried out by amino-terminal sequencing of a protein band released by β-mercaptoethanol (β-ME) from S. cerevisiae mnn9 cell walls. The protein was released also by digestion with β-1,3-glucanases (laminarinase or zymolyase) or by mild alkaline solutions. Deletion of the two carboxyterminal Cys residues (Cys 214 -12aa-Cys 227 -COOH), reduced but did not eliminate incorporation of Pir4 (protein with internal repeats) by disulphide bridges. Similarly, site-directed mutation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 40 publications
2
57
0
Order By: Relevance
“…Although the PIR genes are not essential, strains multiply deleted for PIR1 through PIR4 display additive defects in growth rate, morphology, and sensitivity to cell wall stress agents (Mrsa and Tanner 1999). The Pir proteins are attached directly to b-1,3-glucan chains ( Figure 1) through a linkage that involves their repeat sequences, DGQFQ [where F is any hydrophobic residue (Castillo et al 2003)]. The glucan chain is linked to the protein through the g-carboxyl group of a Glu residue evidently produced through a transglutaminase-type reaction that converts the first Gln residue in the repeat sequence to Glu (Ecker et al 2006).…”
Section: Molecular Structure Of the Yeast Cell Wallmentioning
confidence: 99%
“…Although the PIR genes are not essential, strains multiply deleted for PIR1 through PIR4 display additive defects in growth rate, morphology, and sensitivity to cell wall stress agents (Mrsa and Tanner 1999). The Pir proteins are attached directly to b-1,3-glucan chains ( Figure 1) through a linkage that involves their repeat sequences, DGQFQ [where F is any hydrophobic residue (Castillo et al 2003)]. The glucan chain is linked to the protein through the g-carboxyl group of a Glu residue evidently produced through a transglutaminase-type reaction that converts the first Gln residue in the repeat sequence to Glu (Ecker et al 2006).…”
Section: Molecular Structure Of the Yeast Cell Wallmentioning
confidence: 99%
“…Deletion of all PIR sequences from Pir1 and Pir4 leads to release of these proteins from the cells (Castillo et al 2003;Sumita et al 2005), indicating that the repeats are necessary for wall association. The more repeats, the stronger the binding: deletion of increasing numbers of Pir1's repeats led to release of increasing amounts of Pir1 into the medium (Sumita et al 2005).…”
Section: Incorporation Of Pir Proteins Into the Wallmentioning
confidence: 99%
“…CgPir1-4p have all of the above-described Pir protein features, but CgPir5p has no Kex2p cleavage site, no internal repeats, and a very low pI value compared to CgPir1-4p (Table 2). Since studies with mutated versions of ScPir4p/Cis3p indicated that the presence of the glutamine-rich repetitive sequence is required for its covalent attachment to wall carbohydrates (Castillo et al, 2003), it is uncertain whether CgPir5p can be covalently bound to the cell wall.…”
Section: In Silico Identification Of Putative Mild-alkali-sensitive Pmentioning
confidence: 99%
“…Interestingly, in the C-terminal region of all three GPI-modified CgCwp1 proteins a short sequence similar to the internal repeat sequences of Pir proteins is present. These internal repeats have been shown to be essential for covalent coupling of ScPir4 to the cell wall glycan network (Castillo et al, 2003). Such a sequence is also present in ScCwp1, which has been shown to become linked to the cell wall both through GPI modification and in a mild-alkalisensitive manner (Kapteyn et al, 2001).…”
Section: Mass Spectrometric Identification Of Hf-pyridine-released Prmentioning
confidence: 99%